ІННОВАЦІЙНА ЦИКЛІЧНА МОДЕЛЬ ВИКЛАДАННЯ СОЦІОЛОГІЧНИХ ДИСЦИПЛІН У ЗАКЛАДАХ ВИЩОЇ ОСВІТИ - Шеломовська О. М.; Сорокіна Л. М.; Познанська К. В.; Мачуліна І. І.; Богомаз К. Ю. (International Journal of Innovative Technologies in Social Science, 2019)
The article proposes a process of introducing a cyclic model in the teaching of sociology courses, which allows students to combine the acquisition of theoretical and practical competences, and the teachers to use the latest sociological data in their own teaching activities are absent in modern scientific discourse. According to the authors, the development of a cyclical model of interaction between the teacher and the student gives an opportunity to open new perspectives in the matter of improving the quality of higher education and integration into the world scientific and educational space.